THE EFFECT OF SEMANTIC MAPPING STRATEGY ON STUDENTS’ READING COMPREHENSION AT THE NINTH GRADE STUDENTS OF SMP RAKSANA MEDAN - Situmorang, Resniaty (Kairos English Language Teaching Journal, 2017)
This research is aimed to investigate the effect of semantic mapping strategy on students’ reading comprehension of narrative text and the significant different on reading comprehension of narrative text between two groups: who are teach using semantic mapping strategy and those who are teach using conventional method. The design of the study is experimental study. The population of this study is the ninth grade students of SMP Raksana Medan in the academic year of 2014/2015. The number of the subjects is 60 students. The data are obtained by administering reading test to the IX-1 as experimental group and IX-2 as control group. The research is started by giving pre-test, treatment and post-test to both experimental and control groups. The data of the test are analyzed by using t-test formula to know the difference of the students’ comprehension in reading narrative text between two groups. In the pre-test the mean score of the experimental group is 54 and the control group is 53.67. The result of post-test of the experimental group is 78.33 and the control group is 67.5. The result of the t-test of mean difference is 3.046 and t- table is 2.00 It means that t-value is higher than t-table (3.046 >2.00). The calculation revealed that the hypothesis about a significant difference on reading comprehension between students who are teach narrative text by using semantic mapping strategy and those who are taught by using conventional method is accepted. It can be concluded that Semantic Mapping Strategy worked effectively to help students increase their achievement in reading comprehension. It is suggested that teachers of English apply Semantic Mapping Strategy as one of the alternatives in teaching reading comprehension.